(untitled) (Sociologisk Forskning, 1999)
Welfare regimes and welfare opinions - a comparison of eight western countries The article compares attitudes towards welfare state intervention in eight Western nations, using data from the 1996 module of the International Social Survey Program. Countries are chosen to represent four ”twin pairs”, approximating four ”welfare regimes”: the social democratic (Norway/Sweden), the conservative (Germany/France), the radical (Australia/ New Zealand), and the liberal (Canada/US). The empirical analysis assesses whether levels and group differences in attitudes are structured in a way that reflect distinctions between welfare regimes. It is concluded that while important differences are found between countries, both with regard to aggregated attitudes and with respect to patterns of group differences, these differences only to a limited extent reflect distinctions between welfare regimes. It is suggested that comparative attitude research should pay more attention to how general patterns of conflict, based in the division of labour, are modified by nationally specific institutions.